Autogenic - Prakash Perumal Haridas (2014)
From the void of space, a cube structure comes to life. "AUTOGENIC" is an experimental visual music film that plays with real-time rendering methods, traditional 3D renders and parametric modelling techniques. The film could be regarded as one big experiment in terms of playing with procedural processes and how generative forms can be used as a driving factor for the moving image.